Kam Sen Food and Flushing. - Guo Zijun (Chinese Studies in History)
The article provides information on the history and development of the supermarket Kam Sen Foods in Flushing, New York. It has been noted by the author that the predecessor of Kam Sen Food was an American-style supermarket. The supermarket was opened in September 1981 with only 13 workers. In 1989, business in the Kam Sen was rapidly growing. By 1991, they have transformed the warehouse under the parking lot into an underground market, increasing their business space.